2-amino-4-(3-methyl-3-p-xylylcyclobutyl)1,3-thiazole - Caliskan, N; Dag, C; Soylu, MS; Cukurovali, A; Koksal, NA (Int Union Crystallography, 2006)
In the title compound, C16H20N2S, an intermolecular N-H center dot center dot center dot N hydrogen bond and an N-H center dot center dot center dot pi interaction link two molecules, forming a dimer.
Keywords: 2-Aminothiazole; Cyclobutane